Geodynamic and Isotopic Constraints on the Genesis of Kimberlites, Lamproites and Related Magmas From the Finnish Segment of the Karelian Craton - Dalton, Hayden; Giuliani, Andrea; Hergt, Janet; Phillips, David; O'Brien, Hugh; Ballmer, Maxim D; Maas, Roland; Woodhead, Jon (AMER GEOPHYSICAL UNION, 2022)
Despite the scientific and economic significance of kimberlites and related magmas, their origin is unclear. Here, we address this issue using whole-rock and perovskite-derived Sr-Nd-Hf isotopes for the three occurrences of kimberlite, lamproites and ultramafic lamprophyres (UMLs) in Finland. Mesoproterozoic olivine lamproites at Lentiira-Kuhmo and UMLs at Kuusamo have different isotopic signatures yet were emplaced contemporaneously at 1,200 Ma in response to an extensional regime linked to the Baltica-Laurentia breakup. The low εNd(i) and εHf(i) values of the olivine lamproites are consistent with an enriched subcontinental lithospheric mantle (SCLM) source while UML compositions are intermediate between those of typical kimberlites and lamproites and are interpreted to reflect mixing of asthenospheric melts and ∼10%–15% of melts sourced from metasomatized SCLM. The ∼750 Ma Kuusamo kimberlites, are probably linked to the mantle plume activity that initiated Rodinia's break-up, exhibiting homogenous isotopic compositions which mirror the prominent Geodynamic and Source Constraints for ∼1,200 Ma Olivine Lamproite and Ultramafic Lamprophyre Magmatism in Eastern Finland (PREMA)-like signature of kimberlites globally. By contrast, ∼620–585 Ma Kaavi-Kuopio kimberlites show limited range in εNd(i) and 87Sr/86Sr(i) but have remarkably heterogeneous εHf(i) (+6.5 to −6.3) with a temporal trend toward lower εHf(i) values. While the Kuusamo kimberlites erupted during the early stage of continental break-up, the Kaavi-Kuopio kimberlites were emplaced when Rodinia break-up was completed, coeval with formation of the Central Iapetus large igneous province. Magmas forming the Kaavi-Kupio kimberlites may have formed from an upwelling mantle source similar to PREMA modified by increasing incorporation (up to 10%) of recycled crustal material through time accounting for the trend toward lower εHf(i) in these kimberlites.